PROSPECTS FOR THE USE OF THE BIOLOGICAL METHOD IN NATIONAL PLANT PROTECTION SYSTEMS - Kovtun О.; Tryhuba І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The article discusses the challenges and top priorities of the European Union's common agricultural policy. The focus is on the need to restore biodiversity, promote more ecological and climate-friendly agriculture, and transition from using chemical plant protection methods to biological ones. It is therefore an important objective of the EU to provide farmers with the necessary tools to facilitate such a transition. The task is planned to be solved by promoting the placing on the market of biological plant protection products for farmers, including those who grow organic crops, to create more affordable alternatives for sustainable plant protection. The article also presents a classification of biological control methods proposed by the Commission on Genetic Resources for Food and Agriculture and analyzes scientific sources on the benefits of using each method in Ukraine and globally. Based on the analyzed data from Ukrainian and foreign sources regarding successfully conducted studies on the effectiveness of the use of biological plant protection agents against pests and diseases in Ukraine and the world, the purpose of our study was to analyze the trend of the use of biological plant protection agents in agriculture in the conditions of national production. Changes in the area of agricultural land, separately by regions, and generally across Ukraine, where biological plant protection agents were applied during the research period from 2018 to 2022 were studied. The research results indicate that different trends in the approach to the use of biological control in plant protection systems are observed in different regions of Ukraine. In particular, the lowest trend is observed in the areas of the western regionі, such as Lviv, Ivano-Frankivsk, Volyn, Transcarpathian, Ternopil, and Chernivtsi. At the same time, in such regions as Cherkasy, Kirovohrad, Vinnytsia, Kherson, a positive trend was observed in the change of areas where biological agents were used in plant protection systems.